Development and Validation of a Measurement System for Laparoscopic Surgical Procedures. Issue 4 (1st July 2020) - Ebina, Koki; Abe, Takashige; Komizunai, Shunsuke; Tsujita, Teppei; Sase, Kazuya; Chen, Xiaoshuai; Higuchi, Madoka; Furumido, Jun; Iwahara, Naoya; Kurashima, Yo; Shinohara, Nobuo; Konno, Atsushi
Abstract : This paper presents details of the development and validation of a measurement system for laparoscopic surgical procedures. An individual marker set is attached to each surgical instrument, and hence the developed system can simultaneously track multiple surgical instruments. The tracked surgical instruments can be exchanged during an operation. The movements of surgical instruments such as grasping forceps, scissors forceps, clip appliers, and needle holders are measured, and their tip positions, opening ratios, gripper rotation angles, and orientations are calculated online. Two strain gauges are attached to the gripper of the grasping forceps to measure the grasping point and force. In validation experiments, data from 46 cases of lymphadenectomy and renal parenchyma suturing using porcine cadaver organs performed by 44 subjects were acquired by measurement, and the movements of the surgical instruments used were recorded. A questionnaire survey regarding the operational feel about the surgical instruments was conducted, and the results show that this system has little impact on the operational feel.